Care trajectory management: A conceptual framework for formalizing emergent organisation in nursing practice. (17th July 2018) - Allen, Davina
Abstract : Aim: To offer a new conceptual framework for formalizing nurses' work in managing emergent organisation in health and social care. Background: Much health and social care requires continuous oversight and adjustments in response to contingencies. Nurses have an important role in managing these relationships. Evaluation: A longstanding programme of research on the social organisation of health and social care work provided the foundations for the article. Key issue: Nurses' work in managing emergent organisation may be conceptualized as care trajectory management and factors contributing to trajectory complexity are explored. Conclusions: Care trajectory management is essential for the quality and safety of health and social care but poorly served by existing management frameworks. Implications for Nursing Management: Care trajectory management offers a conceptual framework for the development of new management structures to support an important but poorly supported element of nursing practice.